Geopolitical Competition among Great Powers and ASEAN’s Policy Preference - Chea, Ousaphea (European Scientific Journal, ESJ, 2023)
The United States has long been a security ally and economic partner of the ASEAN member states. Strengths of the U.S.-ASEAN partnership include cooperation on regional security, economic growth, and people-to-people ties. The United States also supports ASEAN's efforts to promote regional cooperation and integration through mechanisms such as the ASEAN Regional Forum and the East Asia Summit. Moreover, the United States has demonstrated its commitment to maintaining a free and open Indo-Pacific region, which is consistent with ASEAN's own aspirations for a rules-based regional order. As China continues to exert influence in the region, ASEAN countries may seek the support of the United States to maintain their sovereignty and territorial integrity. The U.S. factor is regarded as a key factor in the strategic choice of indirect checks and balances against ASEAN. Due to the strategic presence of the United States in the Asia-Pacific region, the United States is considered to play a very important role in ASEAN's soft balancing against China. This Article going to explain the lack of political and security cooperation between China and ASEAN, especially focusing on ASEAN’s security policy towards China.